IMPLEMENTASI METODE ADAPTIVE TYPE-2 FUZZY DAN HISTOGRAM EQUALIZATION UNTUK MEREDUKSI NOISE SALT AND PEPPER PADA CITRA BERTIPE GRAYSCALE - Rito Cipta Sigitta Hariyono; Muamar Fahmi (Informatika Publisher, 2021)
Along with technological developments, images play a very important role as a form of information with the convenience offered in terms of retrieval, processing and storage. Digital image can have a defect (noise) / the main disturbance is salt & pepper type noise which causes the image to experience a decrease in quality. Therefore, it is necessary to improve the quality of digital images (Image enhancement) to improve image quality. The method that can be used to improve image quality (Image Enhancement) is Adaptive Typee-2 Fuzzy. This method will be applied to images containing impulse noise (salt & pepper). This filter consists of two steps, in the first step the pixels are categorized as good or bad. In the second step the pixels that were categorized as bad in the previous step will go through the filter stage. This method is applied to grayscale images to find out how accurate the method is. Based on the discussion, it is found that this method is effective in reducing noise in grayscale-type photographic images, as evidenced by the small value of the Mean Square Error (MSE) and the large value of the resulting Peak Signal to Noise Ratio (PSNR). The average MSE value of the adaptive type-2 fuzzy method is 0.006497218 and the average PSNR value is 24.242225. This method is also better when compared to linear filter methods, for example the Median Filter. The average MSE value of the median filter method is 0.061200481 and the average PSNR value is 17.4459775. The histogram equalization method is applied to the output of the filtering, which is a process that changes the distribution of the grayscale value in an image so that it becomes uniform (uniform). This method is proven to be effective in increasing the distribution of grayscale values so that the output image looks brighter and the details are more visible.